Comparison of Perceptions of Nurses and Premature Infants' Mothers about Mothers' Needs in Neonatal Intensive Care Unit - Seyedeh Zahra Aemmi; Zahra Ahmadi; Tayebeh Reyhani; Hamid Haghani (Tehran University of Medical Sciences, 2013)
Background & Aim: An important goal of nursing care in the Neonatal Intensive Care Unit (NICU) is to provide holistic care as well as the best possible outcome. Understanding perceived needs of mothers is valuable to achieve these goals. This study aimed to compare perceptions of nurses and premature infants' mothers about mothers' needs in the NICUs.   Methods & Materials : This was a cross-sectional study in which 63 nurses and 63 mothers with premature infants were selected from the NICUs of four educational hospitals affiliated to the Mashhad University of Medical Sciences through stratified sampling method in two months. Data were gathered using the NICU Family Needs Inventory of Ward and were analyzed using descriptive-analytical statistical methods in the SPSS v.16.   Results: Among the subscales related to family needs, the following items were reported to be important by mothers: Proximity (95.3%), Assurance (94.1%), Information (91.1%), Support (79.7%) and Comfort (72.8%). On the other hand, nurses believed that the following items were the most important needs of the mothers: Assurance (80.3%), Proximity (75.2%), Information (70.8%), Comfort (66.3%) and Support (64.8%).   Conclusion : According to study findings, nurses should periodically assess needs of the mothers in the NICUs to be aware of the actual needs instead of placing subjective assumptions on mothers needs. This can improve effective communication and interaction with mothers and enhance satisfaction of the mothers with care.